Strategi Implementasi Kebijakan Mal Pelayanan Publik di Kabupaten Purwakarta - Siti Amanah; Sutarto Mochtar; Edah Jubaedah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
The policy of organizing Public Service Mal in Purwakarta Regency Government is a renewal as well as a strategic step in an effort to improve public services that are fast, easy, affordable, safe and comfortable. The purpose of this study is to analyze the implementation of the public service mal policy, internal and external factors that determine policy implementation, and develop a strategy that will be carried out by the Purwakarta Regency Government. Policy implementation model prioritizes four implementation factors, namely: communication, resources, disposition, and bureaucratic structure. Qualitative method is used in this study. Data collection techniques used are interviews, observation and documentation. This study uses a SWOT analysis tool to determine strategies that can be applied by the Purwakarta Regency Government. The results of this study indicate that the implementation of the Public Service Mal policy in Purwakarta Regency has not been optimal. Factors that have not supported the implementation of policies properly are the bureaucratic structure from the SOP aspect and resources that include aspects of human resources and facilities. Internal and external factors that can be considered to formulate a strategy for implementing public service mal policies are: leadership commitment, facilities and infrastructure, strategic location, budget availability, adequate human resources, data integration, regulations, the development of industrial revolution 4.0, geographic location of the community, and community attitudes. According to the SWOT matrix, the Purwakarta Regency Government can use the Strength-Opportunity Strategy (SO Strategy) to take advantage of strengths and opportunities as a top priority through the activities of preparing standard operating procedures, developing information systems, and improving public service mal service facilities. Suggestions of this research are to make decisions of regional heads/regents regarding macro SOPs for public service malls in the form of: manual service SOPs, semi-digital service SOPs, and digital service SOPs to provide legal certainty and alignment with the business processes of public service malls, develop an information system for service malls. public and improve mobile service facilities and independent and/or assisted service facilities